Islamic Historiography of the Nusantara: An Analysis of the Book of Al-Hujjah Karya Kh. Ahmad Hanafiah 1905-1947 - Mustakim; Wahyu Iryana; Uswatun Hasanah (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study examines Al-Hujjah by KH. Ahmad Hanafiah within the perspective of Islamic historiography in the Nusantara, positioning it not only as a religious text but also as a product of the colonial socio-political context. This research aims to analyze the historiographical methods in Al-Hujjah, explore its socio-political background, and identify its contribution to Islamic historiography in Indonesia. This study employs the historical method, including heuristics, source criticism, interpretation, and historiography, using both primary and secondary sources. The findings show that KH. Ahmad Hanafiah integrates sanad, source criticism, and a thematic approach, making Al-Hujjah not only academically valuable but also a medium of awareness and ideological resistance against colonialism. This study concludes that Al-Hujjah contributes significantly to the development of contextual Islamic historiography in Indonesia and highlights the role of ulama in shaping religious and national consciousness.